Transcriptome sequencing reveals regulatory genes associated with neurogenic hearing loss - Fengfeng Jia; Fang Wang; Song Li; Yunhua Cui; Yongmei Yu (BMC Medical Genomics)
Abstract Hearing loss is a prevalent condition with a significant impact on individuals’ quality of life. However, comprehensive studies investigating the differential gene expression and regulatory mechanisms associated with hearing loss are lacking, particularly in the context of diverse patient samples. In this study, we integrated data from 10 patients across different regions, age groups, and genders, with their data retrieved from a public transcriptome database, to explore the molecular basis of hearing loss. These samples are mainly from fibroblasts and keratinocytes. Through differential gene expression analysis, we identified key genes, including ICAM1, SLC1A1, and CD24, which have already been shown to play important roles in neurogenic hearing loss. Furthermore, we predicted potential transcriptional regulatory factors that may modulate the expression of these genes. Enrichment analysis revealed biological processes and pathways associated with hearing loss, highlighting the involvement of circadian rhythm disruption and other neuro-related disorders. Although our study is limited by the sample size and the absence of larger-scale investigations, the identified genes and regulatory factors provide valuable insights into the molecular mechanisms underlying hearing loss. Further molecular and cellular experiments are necessary to validate these findings and elucidate the precise regulatory mechanisms involved. In conclusion, our study contributes to the understanding of hearing loss pathogenesis and offers potential targets for molecular diagnostics and gene-based therapies. This provides a foundation for further research into personalized approaches to diagnosing and treating hearing loss.